Secure execution of unmodified applications on an untrusted host - Baumann, Andrew; Peinado, Marcus; Hunt, Galen; Zmudzinski, Krystof; Rozas, Carlos V.; Hoekstra, Matthew (2013)
Abstract of poster/work-in-progress talk presented at SOSP'13.
SOSP'13: The 24th ACM Symposium on Operating Systems Principles